The effect of physical condition on the artistic gymnastic basic skills - Budiarti, R. (Advances in Social Science, Education and Humanities Research, 2018)
Physical conditions are considered a very important framework to develop physical techniques. The aim of this study is to determine the effect of physical condition in the development of Artistic Gymnastic Basic Skills. The descriptive qualitative method was applied using the survey method. The sample was defined as 100 students, between 7-9 years old from Sleman. Tests and measurements of biomotor (flexibility and power) and gymnastic basic skills (forward roll and bending) were collected as part of the study. The data analysis techniques used was a linear regression. The results of this study have been shown a significant impact of the physical condition on the basic artistic gymnastics skills.